Accounting Information System Literacy at Best Cow Farm Ajung Jember - Khairunnisa, Firstia Nurlaili; Khifdi, M. Yurisul; Riyadi, Anton; Cahyono, Dwi (Universitas Muhammadiyah Jember, 2023)
The purpose of this research is to know and observe the existing accounting information system at Best Cow Farm Ajung Jember. This research is development research. The process of developing an accounting information system often encounters obstacles and becomes a serious problem for a company. The subject of this research is the Best Cow Farm Ajung Jember and the object of this research is the accounting information system of Best Cow Farm Ajung Jember. Data collection methods consist of: interviews, observation and observation. The good or bad performance of an accounting information system can be seen through the satisfaction of users of accounting information systems and the use of the accounting information system itself. The goal to be achieved in this research is to assist partners in supporting their business through an accounting information system in the form of stock input. Through this dedication, it is expected to provide information, knowledge and insight regarding the success of an accounting information system performance